Knowledge Attitude and Practices Towards the Use of Insecticide Treated Mosquito Nets Among Pregnant Women in Lukolo Health Center III Jinja District. - Arthur Muwoya (Student's Journal of Health Research, 2021)
Background: There are an estimated 25 million pregnancies in sub-Saharan Africa at risk of malaria, the consequences of which can be serious for both mother and fetus in terms of morbidity and mortality. The Government of Uganda (GOU) through the Ministry of Health (MOH) and implementing partners like the Global Fund and the Roll Back Malaria initiative were compelled to try to maximize the use of Insecticide Treated Mosquito Nets (ITNs) to mitigate the effects of malaria among vulnerable populations. Methodology: A descriptive cross-sectional survey was used which involved both qualitative and quantitative methods of data collection and it involved 126 (one hundred twenty-six) respondents using self-administered questionnaires.  Data collected was thematically presented and analyzed using descriptive frequencies and percentages using Microsoft excel. Results: This study showed that pregnant mothers' knowledge of the use of insecticide-treated nets was good. However, the respondents' attitude towards the use of Insecticide-treated nets was poor/ negative as up-to 60% of them felt putting on the mosquito net was inconveniencing, 67% didn't think that it was important to sleep under an ITN when one had taken Fansidar at ANC. Also, the practice of pregnant mothers towards the use of ITNs was not good too as only (43%) of the mothers had ITNs. A big number (71%) couldn't afford them, and (10%) believed they didn't need them.  Important to note too, most (57%) mothers continued to use ITNS even when they had holes as, (3%) used it for other things like catching white ants. Conclusions and recommendations: The majority of the pregnant mothers' knowledge of the use of insecticide-treated nets was good as mothers could identify that malaria is transmitted by mosquitoes. The government, through the Ministry of Health, should intensify the free distribution of nets by conducting frequent mass distribution campaigns in the country.